A prototype development for Used Bookshop Portal (UBSP) / Elmaliana Albahari - Albahari, Elmaliana (Faculty of Computer and Mathematical Sciences, 2006)
Used Bookshop Portal (UBSP) is the online delivery of used book listing and information service. UBSP has been set up to give users an easy way of putting their used books back into circulation. This UBSP were there to put buyers and sellers of used books can communicate with each other. This project aims to create a portal where sellers and buyers can come together to buy and sell used books. The Used Book Portal is an alternative approach that allowed user to list the used books that they can buy and sell in others user within this portal. This project is using the behavior of common book portal as an approach, which is allowed user to list, select and view the used book information through online. A user interface for a Used Bookshop Portal was developed using Macromedia Dreamweaver and the interfaces of the system were designed using Adobe Photoshop, SwishMAX and Macromedia Flash MX. PHP: Hypertext Preprocessor is being used as a programming language platform for designing and developing this portal. MySQL is the database programs that been used in this system and it was create for developing and support complete management database. A growing number of web developers are choosing Macromedia Dreamweaver software so quickly and efficiently build scalable, platform independent, web sites and web applications. As the conclusion, a Used Bookshop Portal will take advantage of new content and delivery technology to enable used bookshop portal provide book listing and information service.